Evaluating the impact of added greenery on perceived factors of an urban environment in virtual reality - Ron Bar-Ad; Markel Vigo; Geoffrey Caruso; Qudamah Quboa; Nuno Pinto (PLoS ONE, 2025)
The wellbeing effects of urban greenspace are well established, but may be more attributable to pedestrians’ perceptions than objective levels of greenery. An immersive virtual environment was designed with three levels of roadside greenery: no trees, 200 trees, and 400 trees. Participants were asked to rate each for several perceived and objective factors, and gave their years lived experience in urban, rural, and suburban environments. Trees impacted perceptions of beauty and greenness, and, slightly, building heights. Controlling for urban experience significantly lessened the impact of trees, but showed that perceived greenness had higher significant correlations to all other outcomes.